2010
DOI: 10.1111/j.1524-4725.2010.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recurrence of Trichilemmal Carcinoma of the Scalp in a Young Adult

Abstract: The authors have indicated no significant interest with commercial supporters.T richilemmal carcinoma is a rare, cutaneous adnexal malignant tumor deriving from the outer root sheath of hair follicles. This rare cutaneous cancer usually occurs on the sun-exposed areas of the elderly, 1 although it can appear as multiple lesions on non-sun-exposed skin. 2 Clinically, it may be mistaken for squamous cell carcinoma, basal cell carcinoma, nodular melanoma, or keratoacanthoma. It has been shown to be a malignant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Some clinically aggressive examples of possible TC have, however, been reported. Allee et al 16 and Kulahci et al 17 reported cases of multiple tumour recurrence while Knoeller et al noted a case of lymphatic and skeletal metastasis 18. While these cases may well represent atypically aggressive cases of TC, it again raises questions over histopathological diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinically aggressive examples of possible TC have, however, been reported. Allee et al 16 and Kulahci et al 17 reported cases of multiple tumour recurrence while Knoeller et al noted a case of lymphatic and skeletal metastasis 18. While these cases may well represent atypically aggressive cases of TC, it again raises questions over histopathological diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating trichilemmal cyst likely originates from trichilemmal cysts and typically leads to trauma or inflammation [5]. The distribution of lesions tends to suggest that sunlight plays an important role in the development of this malignancy [11]. Most trichilemmal tumors have been known to occur in heat-bearing and/or sun-exposed areas of elderly persons, without a sex predilection [12].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating trichilemmal tumor generally has a nonaggressive course and can be treated with wide excision with the demonstration of clear margins [11]. Complete surgical excision and accurate follow-up in all cases of PTT are recommended because local relapses and metastatic spread are possible and the biological behavior of this neoplasm seems to be difficult to predict [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations